1976
DOI: 10.1210/jcem-43-6-1382
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone and Prolactin Release in Acromegalic Patients Following Metergoline Administration

Abstract: In six acromegalite patients oral administration of 4 mg of metergoline, an antiserotonin agent, produced a fall in plasma growth hormone (GH) and prolactin (PRL) concentrations. In the same patients this inhibitory effect was observed after administration of dopaminergic drugs, L-Dopa and 2-Br-alpha-ergocryptine. Both GH and PRL levels remained suppressed during a 6 day course of treatmnt with metergoline. These results are consistent with the hypothesis that the inhibitory effect of netergoline on GH and PRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…However, at variance with Br [Camanni et al, 1975], and other dopaminergic agonists such as L-dopa [Boyd et a!., 1970] and apomorphine [L al et al, 1973], antiserotonin drugs fail to stimulate GH release in normal subjects [Bivens et al, 1973;P o al., 1975; L al et al, 1977]. The Prl-lowering effect of Met observed in normals is virtually superimposable on that reported in acromegalic patients D elitala et al, 1976] and confirms our previous report that short-term treatment with the drug reduces basal and TRH-stimulated Prl levels in normal man [F er r a r i et al, 1976]. The finding that Meth also decreases serum Prl concen tration is in agreement with the data by M endelson et al [1975] showing that treatment with this drug inhibits Prl secretion.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, at variance with Br [Camanni et al, 1975], and other dopaminergic agonists such as L-dopa [Boyd et a!., 1970] and apomorphine [L al et al, 1973], antiserotonin drugs fail to stimulate GH release in normal subjects [Bivens et al, 1973;P o al., 1975; L al et al, 1977]. The Prl-lowering effect of Met observed in normals is virtually superimposable on that reported in acromegalic patients D elitala et al, 1976] and confirms our previous report that short-term treatment with the drug reduces basal and TRH-stimulated Prl levels in normal man [F er r a r i et al, 1976]. The finding that Meth also decreases serum Prl concen tration is in agreement with the data by M endelson et al [1975] showing that treatment with this drug inhibits Prl secretion.…”
Section: Discussionmentioning
confidence: 90%
“…In this respect, and also in reducing serum GH levels in some acro megalics D elitala et al, 1976;F eldm a n et al, 1976], these drugs are quite similar to the potent dopaminergic inhibitor of Prl secretion, Br [D el Pozo et al, 1972]. A Prl-lowering effect of acutely admin istered Met in normal subjects was also recently reported by D elitala et al [1977c] who also found that this drug is as potent as Br in reducing Prl release.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the variation in baseline prolactin in the latter study made the changes difficult to interpret, and it has been argued that pimozide has a direct action on the entrance of calcium into the cell which is not shown by other dopamine antagonists. Our data suggest that the effectiveness of metergoline in vivo in lowering prolactin levels (Delitala et al, 1976) may not be of a true dopaminergic mechanism and is independent of 5-HT receptors at least at the pituitary level. Since cyproheptadine and metergoline suppress prolactin by a mechanism that appears to be neither 5-hydroxytryptaminergic nor dopaminergic, this must be taken into account in any investigation using these agents as pharmacological tools.…”
mentioning
confidence: 72%
“…However, the suppression of prolactin and growth hormone secretion in man by metergoline (Delitala, Masala, Alagna, Devilla & Lotti, 1976) and the inhibition of dihydroergocryptine binding in rat pituitaries by cyproheptadine (Caron, Beaulieu, Raymond, Gagne, Drouin, Lefkowitz & Labrie, 1978) have been taken to indicate that both agents may also be dopamine agonists. We present data showing that cyproheptadine and methergoline readily and reversibly suppress the release of prolactin from dispersed rat anterior pituitary cells and that this effect is not antagonized by either 5-HT or a *variety of dopamine antagonists.…”
mentioning
confidence: 99%